RELIEF FROM COMMUNICATION: PARENTAL SURVEILLANCE TECHNOLOGIES, TRUST AND CARE - Damkjær, Maja Sonne; Southerton, Clare Victoria; Albrechtslund, Anders (AoIR Selected Papers of Internet Research, 2019)
The everyday adoption of digital technologies such as mobile phones and social media has had transformative effects on interactions within the family (Clark, 2013), as families become increasingly dependent on their capacities for coordinating day-to-day activities and maintaining intimate relationships (Licoppe, 2004; Ling, 2014). Concurrently, these technologies enable new forms of surveillance, allowing parents to observe their children’s movements and interactions remotely, eg. via GPS-apps (Marx & Steeves, 2010), as well as lateral forms of surveillance embedded in social media practices like ‘Facebook stalking’ (Albrechtslund, 2013). This paper explores how the surveillant capacities of communication technologies are involved in shaping relations of trust in the family, drawing on empirical data from in-depth interviews with adolescents at two schools and 17 Danish families conducted during 2017. Despite surveillance often being represented as a practice which undermines trust (Mayer, 2003; Neyland, 2006; Rooney, 2010), our findings suggest that the relationship between trust and surveillance, for the families in our study, was far less straightforward. Surveillance was an important part of care practices for parents and, in some instances, tracking technologies were able to offer a kind of ‘relief’ from social pressures to remain in contact. This paper explores the perceptions of parents and adolescents regarding using communication technologies for surveillance, to examine the nuanced constitution of trust occurring.